Redefine and practice our peace, our security, if they do theirs - Muto, Ichiyo (Social justice, 2000)
Part of a special issue on neoliberalism, militarism, and armed conflict. An article based on a speech presented to the International Forum on People's Security, which was held in Okinawa, Japan, on June 29–July 2, 2000. The writer discusses people's security, justice, peace and the action needed throughout Asia and beyond to attain them. He comments on the U.S.-Japan alliance, globalization processes and U.S. military strategy, peace movements and the cold war context, the need to redefine security, and the United Nations Development Program's concept of human security.